HUBUNGAN ANTARA KONSENTRASI ASAM URAT SERUM DENGAN RESISTENSI INSULIN PADA PENDUDUK SUKU BALI ASLI DI DUSUN TENGANAN PEGRINGSINGAN KARANGASEM - Ngurah Wises, Ida Bagus; Suastika, Ketut (journal of internal medicine; Vol. 10, No. 2 Mei 2009)
Elevated serum uric acid concentrations are commonly seen in association with individual cardiovascular risk factor such as hypertriglyseridemia, hypertension, obesity, and hyperglycemia, a cluster that, when found together in the same person, characterizes the so-called metabolic syndrome. The original conceptualization of this syndrome was on the basis of resistance to the actions of insulin. The reduction of endothelial nitric oxide bioavailability and the production of reactive oxygen species by uric acid may be the mechanism for insulin resistance. Otherwise insulin has a physiological action on renal tubules by stimulating reabsorption of sodium and urate, resulting an increase in serum uric acid levels. In this condition, HOMA-IR was the model which is a convenient means of evaluating insulin resistance. To know the association between serum uric acid concentration and insulin resistance, a cross sectional analytic study was conducted on Balinese in Tenganan region between Desember 2007 and January 2008. The study involved 80 participants age of 18-65 years old, agree to participate by informed consent. Serum concentration of insulin was measured by immunoassay method, plasma glucosa, serum uric acid, HDL-cholesterol, trigycerides, serum creatinin, were determined by enzymatic procedure after overnight fast. Descriptive statistic analysis on numeric data presented as mean ± SD, nominal and ordinal data in proportion. Inferential statistic analysis with bivariate KendallÕs tau correlation and simple logistic regression was performed and multiple logistic regression was used to know the independency of its association. Of 80 eligible samples, 39 (49%) men, and 41 (51%) women, mean age was 41.73 ± 12.41 yo, mean of waist circumference was 77.99 ± 10.91 cm, mean of serum uric acid concentration was 5.49 ± 1.38 mg/dL, mean of plasma glucosa was 92.04 ± 8.79 mg/dL, median of insulin was 2.70 (2.00 Ð 17.90) mIU/mL, median of HOMA-IR was 0.685 (0.38-4.10), mean of HDL cholesterol was 59.19 ± 14.01 mg/dL, and median of triglycerides was 122.50 (48 Ð 369) mg/dL. In univariate analysis, the insulin resistance were positively correlated with serum uric acid, waist circumference, and triglycerides (r= 0.234; P = 0.003), (r = 0.269; P = 0.001), and (r = 0.153; P = 0.046) respectively and negatively with HDL cholesterol (r = -0.297; P = 0.009). In multivariate analysis with multiple logistic regression both the 2nd tertile of uric acid (4,7 Ð 6,6 mg/dL) and waist circumference were independently associated with the insulin resistance (PR 3.97; IK 95% : 1.273 Ð 12.386; P = 0.018), and (PR 5.79; IK 95% : 1.417 Ð 23.650; P = 0.014) respectively. Conclusion: There is association between serum uric acid concentration and insulin resistance, and both the 2nd tertile of uric acid and waist circumference are independently and significantly associated with insulin resistance.
Keywords: uric acid, insulin, HOMA-IR